Water delivery from cores to disks: deuteration as a probe of the prestellar inheritance of H2O - Furuya, Kenji; Harsono, Daniel (Astronomy and astrophysics, 2017)
We investigate the delivery of regular and deuterated forms of water from prestellar cores to circumstellar disks. We adopt a semi-analytical, axisymmetric, two-dimensional collapsing core model with post-processing gas-ice astrochemical simulations, in which a layered ice structure is considered. The physical and chemical evolutions are followed until the end of the main accretion phase. In our models, when mass averaged over the whole disk, a forming disk has a similar H2O abundance and HDO/H2O abundance ratio (within a factor of 2) as the precollapse values of these quantities, regardless of time. Consistent with previous studies, our models suggest that interstellar water ice is delivered to forming disks without significant alteration. On the other hand, the local vertically averaged H2O ice abundance and HDO/H2O ice ratio can differ more, by up to a factor of several, depending on time and distance from a central star. Key parameters for the local variations are the fluence of stellar UV photons en route into the disk and the ice layered structure, the latter of which is mostly established in the prestellar stages. We also find that even if interstellar water ice is destroyed by stellar UV and (partly) reformed prior to disk entry, the HDO/H2O ratio in reformed water ice is similar to the original value. This finding indicates that some caution is needed in discussions on the prestellar inheritance of H2O based on comparisons between the observationally derived HDO/H2O ratio in clouds/cores and that in disks/comets. Alternatively, we propose that the ratio of D2O/HDO to HDO/H2O better probes the prestellar inheritance of H2O. It is also found that in forming disks icy organics are more enriched in deuterium than water ice. The differential deuterium fractionation in water and organics is inherited from prestellar stages.